Factorise x2+2x+1-9y2
Answers
Answer:
= (x + 3y + 1) (x – 3y + 1)
Step-by-step explanation:
= x2 + 2x + 1 - 9y2
= (x + 1)2 – (3y)2
= (x + 3y + 1) (x – 3y + 1)
MARK ME AS BRAINLIST!
The answer to the factorisation is, (x+3y+1) (x-3y+1)
Given : The algebraic expression is, x²+2x+1-9y²
To find : The factorisation of the given algebraic expression.
Solution :
We can simply solve this mathematical problem by using the following mathematical process. (our goal is to factorise the given algebraic expression)
Here, we will be using general algebraic method.
So,
= x²+2x+1-9y²
= (x²+2x+1) - (9y)²
= {(x)²+(2×x×1)+(1)²} - (3y)²
= (x+1)² - (3y)²
= (x+1+3y) (x+1-3y)
= (x+3y+1) (x-3y+1)
(This will be considered as the final result.)
Used formula :
- x²+2xy+y² = (x+y)²
- x²-y² = (x+y) (x-y)
Hence, the answer to the factorisation is, (x+3y+1) (x-3y+1)